Bismaleimide resin as well as preparation method and application thereof

By designing a liquid bismaleimide resin at room temperature, the high melting point and complex processing problems of BMI resin are solved, and its stability and mechanical properties at high temperatures are improved, and better process performance and application potential are achieved. .

CN119306648AInactive Publication Date: 2025-01-14HANGZHOU ZHIJIANG SILICONE CHEM +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411855704.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The high melting point, low solubility, complex processing process, and high existing bismaleimide (BMI) resins lead to poor process performance, high cost and poor recyclability, and face market competition pressure.

Method used

Design a liquid bismaleimide resin at room temperature, and form high saturation maleimide groups and alkyl chains through specific structural design and synthesis methods to improve its stability at high temperatures. and processability, and form a three-dimensional network structure through thermal crosslinking to enhance mechanical properties.

Benefits of technology

It achieves excellent stability and chemical resistance of BMI resin, improves its mechanical properties and thermoplastic properties at high temperatures, reduces processing difficulty, and expands its application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306648A_ABST
    Figure CN119306648A_ABST
Patent Text Reader

Abstract

The invention provides bismaleimide resin as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials, the bismaleimide resin has a structure as shown in a formula I. The bismaleimide resin has excellent stability and chemical resistance at high temperature, and can be applied to the field of high polymer materials. The material has good mechanical properties and high temperature resistance, is liquid at room temperature, has good processability, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a bismaleimide resin and a preparation method and application thereof. Background Art

[0002] Bismaleimide (BMI) resin is a polyimide material with active end groups at both ends of the molecule. It has the characteristics of high temperature resistance, heat and humidity resistance, low moisture absorption rate, chemical corrosion resistance, radiation resistance, excellent mechanical and electrical properties, etc. BMI is widely used in aerospace, automobile, semiconductor manufacturing, electronic packaging and other fields in the form of resin matrix of advanced composite materials, high temperature resistant insulation materials, adhesives, coatings, membrane materials, fibers, etc. For example, due to its good electrical insulation, excellent mechanical strength and high dimensional stability, BMI is widely used in the field of copper clad laminate materials.

[0003] At present, commercial BMI resin has a high melting point, poor solubility, and high molding temperature, resulting in poor process performance. In addition, the molecular structure is highly symmetrical, contains a large number of heterocycles, and has high rigidity. Therefore, the cross-linking density after molding and curing is poor, and toughness is poor. In actual application, toughening modification is required to meet specific needs. In addition, BMI resin has some other problems: 1. High cost: The production cost of BMI resin is relatively high, which makes it may not be the most economical choice in some applications. This may be a constraint for some large-scale production and cost-sensitive industries. 2. Difficult processing: The processing of BMI resin is relatively complicated, requiring high-temperature melting or environmentally unfriendly solvents for dissolution. This makes the processing process complicated and limits certain applications. 3. Recyclability: BMI resin is usually cured at high temperature, which may affect its recyclability. In some fields with high requirements for sustainability and circular economy, this may be a consideration. 4. Market competition: With the continuous emergence of new high-performance resins, BMI resin faces competitive pressure in the market. Therefore, continuous improvement and innovation are needed to remain competitive. Summary of the invention

[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a bismaleimide resin and a preparation method and application thereof. The bismaleimide resin of the present invention is liquid at room temperature, which gives it better processability and is a high-performance BMI resin material.

[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0006] In one aspect, the present invention provides a bismaleimide resin having a structure as shown in Formula 1 below:

[0007]

[0008] Formula 1

[0009] Wherein, R1 is selected from C1-C5 alkylene, preferably -CH2-, -CH2-CH2- or -C5H 10 .

[0010] In the present invention, in the bismaleimide resin having the structure shown, two maleimide groups are distributed at both ends, the structure contains double bonds, and its saturation is relatively high. The resin is endowed with excellent stability and chemical resistance at high temperatures. During the hardening process, the BMI resin forms a three-dimensional network structure through thermal crosslinking, which enhances its mechanical properties and high temperature resistance. This crosslinked structure helps to improve the thermoplasticity of the resin. And the structural design of the BMI resin can adjust its performance by changing the alkyl chain length to meet the requirements of different engineering applications. This adjustability makes the resin have a wide range of application potentials in different fields.

[0011] Preferably, the bismaleimide resin is selected from any one of the following resins:

[0012] , ,

[0013] .

[0014] On the other hand, the present invention provides a method for preparing the bismaleimide resin as described above, the preparation method comprising the following steps:

[0015] The compound represented by formula A reacts with the compound represented by formula B to obtain the bismaleimide resin represented by formula 1. The reaction formula is as follows:

[0016] ;

[0017] Wherein R1 is selected from C1-C5 alkylene, preferably -CH2-, -CH2-CH2- or -C5H 10 .

[0018] Preferably, the molar ratio of the compound represented by formula A to the compound represented by formula B is 3:1-6:1, for example 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1.

[0019] Preferably, the reaction is carried out in the presence of a dehydrating agent.

[0020] Preferably, the molar ratio of the compound represented by formula A to the dehydrating agent is 1:1-1:2, for example, 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.7, 1:1.8, 1:1.9 or 1:2.

[0021] Preferably, the dehydrating agent is selected from at least one of N,N'-dicyclohexylcarbodiimide (DCC), diisopropylcarbodiimide (DIC) or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDCI).

[0022] Preferably, the reaction is carried out in the presence of a catalyst.

[0023] Preferably, the catalyst is selected from at least one of 4-dimethylaminopyridine (DMAP), 4-pyrrolidinylpyridine, hydroxybenzotriazole or diphenylamine trifluoromethanesulfonate.

[0024] Preferably, the molar ratio of the catalyst to the compound represented by formula B is 1:10-1:15, for example 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.

[0025] Preferably, the reaction temperature is room temperature (15-35°C, such as 15°C, 18°C, 20°C, 25°C, 28°C, 30°C, 33°C or 35°C) and the reaction time is 12-24h, such as 12h, 13h, 15h, 18h, 20h, 22h or 24h.

[0026] In another aspect, the present invention provides use of the bismaleimide resin described above in the preparation of a thermosetting material.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The bismaleimide resin of the invention has excellent stability and chemical resistance at high temperatures, good mechanical properties and high temperature resistance, is liquid at room temperature, has good processability, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The compound prepared in Example 1 1 H NMR spectrum.

[0030] Figure 2 The compound prepared in Example 2 1 H NMR spectrum.

[0031] Figure 3 This is the 1H NMR spectrum of the compound prepared in Example 3. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0033] Example 1

[0034]

[0035] Dissolve maleimide acetic acid (232.5g, 1.5mol) in 2500ml dichloromethane, then dissolve dicyclohexylcarbodiimide (DCC) powder (309g, 1.5mol) in 300ml dichloromethane. Slowly add the DCC solution to the maleimide propionic acid solution under stirring. After all the additions are completed, continue stirring and reacting for 10min. Then add bis(hydroxymethyl)tricyclo[5.2.1.02,6]decane (TCD) (98g, 0.5mol) to the system; finally, slowly add 4-dimethylaminopyridine (DMAP) powder (6.1g, 0.05mol) and stop the reaction after 8h. Filter and remove insoluble matter, take the filtrate and extract it with water in a separatory funnel, combine the organic layers, dry them over anhydrous Na2SO4, spin dry the filtrate to obtain a red viscous liquid, and a small amount of solid precipitates after standing and cooling. Filter again to obtain the final product.

[0036] The product was characterized by H NMR spectroscopy. Figure 1 As shown, its NMR data are as follows: 1 H NMR (500 MHz, deuterated chloroform) δ 6.73 (s, 4H), 4.55 (d, J = 1.6 Hz, 4H), 4.12 (dd, J = 3.8,1.1 Hz, 2H), 4.05 (d, J = 4.6 Hz, 2H), 2.36 – 2.13 (m, 4H), 2.12 – 2.03 (m,2H), 1.89 – 1.81 (m, 1H), 1.67 – 1.38 (m, 7H).

[0037] Example 2

[0038]

[0039] Dissolve maleimide propionic acid (253.5g, 1.5mol) in 2500ml dichloromethane, then dissolve dicyclohexylcarbodiimide (DCC) powder (309g, 1.5mol) in 300ml dichloromethane. Slowly drop the DCC solution into the maleimide propionic acid solution under stirring. After all the additions are completed, continue stirring and reacting for 10min. Then add TCD (98g, 0.5mol) into the system; finally, slowly add 4-dimethylaminopyridine (DMAP) powder (6.1g, 0.05mol) and stop the reaction after 8h. Filter and remove insoluble matter, take the filtrate and extract it with water in a separatory funnel, combine the organic layers, dry them over anhydrous Na2SO4, spin dry the filtrate to obtain a red viscous liquid, and a small amount of solid precipitates after standing and cooling. Filter again to obtain the final product.

[0040] The product was characterized by H NMR spectroscopy. Figure 2 As shown, its NMR data are as follows: 1 H NMR (500 MHz, deuterated chloroform) δ 6.64 (s, 4H), 4.15 – 4.00 (m, 8H), 2.68 (t, J = 6.3 Hz, 4H),2.33 – 2.29 (m, 1H), 2.29 – 2.25 (m, 1H), 2.22 (dp, J = 6.4, 4.0 Hz, 1H),2.16 (qt, J = 5.5, 3.8 Hz, 1H), 2.13 – 2.01 (m, 2H), 1.88 – 1.81 (m, 1H),1.61 (ddd, J = 12.3, 5.4, 4.1 Hz, 1H), 1.58 – 1.42 (m, 6H).

[0041] Example 3

[0042] Synthesis of compounds:

[0043] Dissolve maleimidocaproic acid (316.5 g, 1.5 mol) in 2500 ml of dichloromethane, then dissolve dicyclohexylcarbodiimide (DCC) powder (309 g, 1.5 mol) in 300 ml of dichloromethane. Slowly drop the DCC solution into the maleimidocaproic acid solution under stirring. After all the additions are completed, continue stirring and reacting for 10 min. Then add TCD (98 g, 0.5 mol) into the system; finally, slowly add 4-dimethylaminopyridine (DMAP) powder (6.1 g, 0.05 mol) and stop the reaction after 8 h. Filter and remove the insoluble matter, take the filtrate and extract it with water in a separatory funnel, combine the organic layers, dry them over anhydrous Na2SO4, spin dry the filtrate to obtain a red viscous liquid, and a small amount of solid precipitates after standing and cooling. Filter again to obtain the final product BMI-TCD.

[0044] The product was characterized by H NMR spectroscopy. Figure 3 As shown, its NMR data are as follows: 1 H NMR (600 MHz, deuterated chloroform) δ 6.63 (s, 4H), 3.91 – 3.71 (m, 4H), 3.44 (t, J = 7.3 Hz, 4H),2.25 – 2.19 (m, 4H), 2.13 – 1.99 (m, 2H), 1.99 – 1.91 (m, 3H), 1.77 – 1.11(m, 21H), 0.87 (dp, J = 15.6, 4.4 Hz, 1H).

[0045] Comparative Example 1

[0046] BMI-PPG400 disclosed in CN117844435A was used as comparative compound 1.

[0047] Comparative Example 2

[0048] BMI-PPG1000 disclosed in CN117844435A was used as comparative compound 2.

[0049] The application examples and comparative proportions are divided into three cases: A, B, and C for comparison.

[0050] Case A The preparation of the insulating adhesive is as follows (Comparative Example 1):

[0051] Weigh 3 parts of the BMI resin of the embodiment and the comparative example respectively and add them to a dispersion container, then add 8 parts of cyanate ester-L10 (Hubei Jiahui Xingcheng Biotechnology Co., Ltd.), 0.1 part of TPP powder (Aladdin Chemical Reagent), 0.1 part of silane coupling agent KH570 (Shandong Huachen New Materials Co., Ltd.), and stir manually until the powder is completely dissolved; mix at 1000rpm in a high-speed disperser for 10 min until it is completely clarified; then add 11.2 parts of silica SE6050-SEG (Admatech) and 0.2 parts of fumed silica TS720 (Cabot), disperse at 1200 rpm for 5 min and at 1800rpm for 10 min; turn on the vacuum, vacuum degree <-0.098 MPa, degas at 1800rpm for 10 min; discharge at normal pressure to prepare insulating adhesive samples.

[0052] Comparative Example 2 provides an insulating adhesive, wherein the compound BMI-PPG400 in Comparative Example 1 is replaced by an equal amount of BMI-PPG1000, and other raw material components and amounts are shown in Table 1. The preparation method is the same as that of Comparative Example 1.

[0053] Application Example 2 provides an insulating adhesive, wherein the compound BMI-PPG400 in Comparative Example 1 is replaced with an equal amount of BMI-PPG1000, and other raw material components and amounts are shown in Table 1. The preparation method is the same as that of Comparative Example 1.

[0054] The composition and performance test results of the insulating glue of case A are shown in Table 1.

[0055] Table 1

[0056]

[0057] Case B: The preparation of the insulating adhesive is as follows (Comparative Example 3 and Example 2)

[0058] Comparative Example 3: Weigh 3 parts of solid powder BMI resin and add them to a dispersion container, then add 10 parts of NMP and stir manually until the solid resin is completely dissolved and the solution is clear and transparent; then add 12 parts of cyanate-L10, 0.02 parts of copper acetylacetonate, and 0.6 parts of nonylphenol, and disperse at 1000 rpm in a high-speed disperser for 10 min; finally add 15.6 parts of silica FE920A-SQ, disperse at 1200 rpm for 5 min and at 1800 rpm for 10 min; turn on the vacuum, the vacuum degree is <-0.098MPa, 1800rpm.

[0059] Application Example 2: 0.02 parts of copper acetylacetonate and 0.6 parts of nonylphenol were weighed into a dispersion container and stirred manually until the solid was completely dissolved. Then, 3 parts of BMI-TCD and 12 parts of cyanate-L10 (Hubei Jiahui Xingcheng Biotechnology Co., Ltd.) were added and dispersed in a high-speed disperser at 1000 rpm for 10 min. Finally, 15.6 parts of silica FE920A-SQ were added and dispersed at 1200 rpm for 5 min and at 1800 rpm for 10 min. The vacuum was turned on, the vacuum degree was <-0.098 MPa, and the mixture was degassed at 1800 rpm for 10 min. The material was discharged at normal pressure to obtain an insulating adhesive sample.

[0060] The composition and performance test results of the insulating glue of case B are shown in Table 2.

[0061] Table 2

[0062]

[0063] Case C: The conductive adhesive is prepared as follows (Comparative Example 4 and Application Example 3)

[0064] Take Application Example 3 as an example: weigh 5 parts of BMI-TCD and add them to a dispersion container, then add 12 parts of cyanate ester-L10 (Hubei Jiahui Xingcheng Biotechnology Co., Ltd.), 2 parts of cardanol phenolic resin NX4004 (Cardoite), 0.2 parts of imidazole accelerator 2E4MZ (Shikoku Chemical (Japan)), 0.1 parts of peroxide CHPO (Aladdin Biochemical Technology Co., Ltd.), and mix them in a high-speed disperser at 1000 rpm for 10 min; then add 57.9 parts of silver powder EA-0295 (MetalorTechnologies USA), disperse at 1200 rpm for 5 min, and disperse at 1800 rpm for 10 min; turn on the vacuum, vacuum degree <-0.098 MPa, degas at 1800 rpm for 10 min; discharge at normal pressure to obtain a conductive adhesive sample.

[0065] Comparative Example 4 provides an insulating adhesive, wherein the compound BMI-TCD in Application Example 3 is replaced by an equal amount of BMI-PPG400, and other raw material components and amounts are shown in Table 3. The preparation method is the same as that of Application Example 3.

[0066] The performance test data is shown in Table 3.

[0067] Table 3

[0068]

[0069] The performance testing method in the present invention is as follows:

[0070] (1-1) Volume resistivity test (applicable to insulating adhesive):

[0071] Refer to the national standard GB / T 1410-2006 "Test method for volume resistivity and surface resistivity of solid insulating materials".

[0072] Preparation of test pieces: A circular test piece with a thickness of 2 mm and a diameter of 80 mm was prepared by filling a polytetrafluoroethylene mold and pressing. Curing conditions: The test piece was placed in an oven and heated from 25 °C to 40 °C at a rate of 5 °C / min. o C to 175℃, then 175℃×60min; demoulding after cooling down. Test equipment: ZC36 high insulation resistance measuring instrument (Shanghai Precision Instrument Co., Ltd.).

[0073] (1-2) Volume resistivity test (applicable to conductive adhesive):

[0074] Refer to the four-probe method of the industry standard "HG / T 5912-2021 Conductive Adhesives".

[0075] Preparation of conductive film: On a glass substrate, a conductive film with a thickness of ~25 μm, a width of 9 mm, and a length of 50 mm was prepared by a controlled thickness tape scraping method.

[0076] Curing conditions: The specimen was placed in an oven and heated from 25°C to 175°C at a heating rate of 5°C / min, and then kept at 175°C for 60 min.

[0077] Test equipment: TH2516 DC resistance tester from Changzhou Tonghui Electronics Co., Ltd.

[0078] (2) Moisture absorption rate:

[0079] Refer to the national standard "GB / T35494.1-2017".

[0080] Sample size: 2 cm×1 cm×50~100 μm (thickness); place the sample in an oven at 105℃~120℃ and dry for 1 h~4 h, take it out and weigh it as the initial mass; 3 samples are collected in a group.

[0081] After curing for 168 h under double 85 conditions (constant temperature and humidity chamber, 85% relative humidity and 85°C), the glue was cooled to room temperature and weighed on a balance. The moisture absorption rate of the cured glue was calculated based on the mass change (the arithmetic mean value was taken).

[0082] Equipment: Dual 85 high and low temperature humidity test chamber: KTM-THB515E (Temujin Electronic Technology (Kunshan) Co., Ltd.

[0083] (3) Chip thrust:

[0084] The test method refers to "HG / T 5912-2021 Conductive Adhesives".

[0085] The size of the silicon wafer is: 2 mm × 2 mm (thickness 500um); the substrate is a silver-plated copper sheet.

[0086] Curing conditions: The test piece was placed in an oven and heated from 25 o The temperature was raised from 175°C to 175°C, and then kept at 175°C for 60 min. The testing equipment was a DAGE-4000P multifunctional push-pull testing machine (Nordson DAGE Precision Industries LTD, USA) with a temperature-controlled heating table. The shear strength was the thrust force (in kgF, kilogram-force). Ten test data were taken from the test samples corresponding to each type of glue, and the arithmetic mean of the results was taken.

[0087] When measuring high-temperature thrust, set the temperature on the temperature-controlled heating platform, wait for the target temperature to be reached and stabilize for 5 minutes before starting to measure the thrust.

[0088] (4) Residual glue rate on broken ring surface:

[0089] Destruction surface evaluation: After the chip thrust test is completed, the substrate is placed on the microscope stage and the residual glue on the substrate after the thrust damage is observed through an optical microscope. The residual glue area ratio (percentage relative to the chip area) is evaluated for assessment. The score is based on a 10-point system, 100% residual glue corresponds to 10; 90% residual glue corresponds to 9, and so on. 10% residual glue corresponds to 1; 0% residual glue corresponds to 0; the arithmetic average of 10 samples is taken.

[0090] Testing equipment: Shanghai Optical Instrument Factory-6XM-PC metallographic microscope. The higher the residual glue rate, the better the bonding performance.

[0091] (5) Chip warping

[0092] A silver-plated frame is used, the chip size is 9 mm×9 mm, and the chip / frame is baked and cured in an oven after the glue is dispensed by drawing lines.

[0093] Curing conditions: The test piece was placed in an oven and heated from 25 o C to 175℃, and then keep at 175℃ for 60 min.

[0094] The warpage is obtained by measuring the surface roughness along the diagonal direction of the chip. The unit is μm. If it is less than 20 μm, it is considered to have passed the test; if it exceeds 20 μm, it is considered to have failed.

[0095] Test equipment: KEYENCE VHX-970FN digital microscope system.

[0096] Data discussion section:

[0097] Case A series: After BMI-TCD replaced BMI-PPG400, the normal temperature chip thrust was significantly improved, which was increased by 24% and 45% compared with the comparison of 1 / 2. High temperature 160 o C improved more significantly, by 84% and 118%. However, the residual adhesive on the damaged surface still reached 100%. There was also a slight improvement in moisture absorption rate.

[0098] Case B series: In Application Example 2, liquid BMI-TCD is used, which eliminates the need to dissolve BMI with solvent, thus improving process efficiency. The normal temperature chip thrust is 3.7 times higher than that of Comparative Example 3. In Comparative Example 3, the solvent NMP evaporates during the curing process, forming voids, which may be the reason for the relatively low thrust. The high temperature 160 o The C thrust has been slightly improved. The residual adhesive on the damaged surface has also been greatly improved. The moisture absorption rate and volume resistivity have also been improved.

[0099] Case C series: Application Example 3 shows a 16% increase in normal temperature chip thrust compared to Comparative Example 4. High temperature 160 o The C thrust has been greatly improved from 6kgF to 11.2kgF. The improvement in bonding strength may be related to the rigid ring structure in the BMI-TCD molecular structure. The residual adhesive on the damaged surface is basically maintained. There is also improvement in volume resistivity, and the chip warping test is equivalent to that of comparative example 3.

[0100] The applicant declares that the present invention illustrates the bismaleimide resin and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A bismaleimide resin, characterized in that The bismaleimide resin has a structure as shown in Formula 1: ; Formula 1 Wherein, R1 is selected from C1-C5 alkylene.

2. The bismaleimide resin according to claim 1, characterized in that R1 is selected from -CH2-, -CH2-CH2- or -C5H 10 .

3. The bismaleimide resin according to claim 1, characterized in that The bismaleimide resin is selected from any one of the following resins: 、 、 。 4. The method for preparing a bismaleimide resin according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The compound represented by formula A reacts with the compound represented by formula B to obtain the bismaleimide resin represented by formula 1. The reaction formula is as follows: ; Wherein, R1 is selected from C1-C5 alkylene.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the compound represented by formula A to the compound represented by formula B is 3:1-6:

1.

6. The preparation method according to claim 4, characterized in that: The reaction is carried out in the presence of a dehydrating agent; The molar ratio of the compound represented by formula A to the dehydrating agent is 1:1-1:2; The dehydrating agent is selected from at least one of N,N'-dicyclohexylcarbodiimide, diisopropylcarbodiimide or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.

7. The preparation method according to claim 4, characterized in that: The reaction is carried out in the presence of a catalyst; The catalyst is selected from at least one of 4-dimethylaminopyridine, 4-pyrrolidinopyridine, hydroxybenzotriazole or diphenylamine trifluoromethanesulfonate.

8. The preparation method according to claim 7, characterized in that: The molar ratio of the catalyst to the compound represented by formula B is 1:10-1:

15.

9. The preparation method according to claim 4, characterized in that: The reaction temperature is room temperature and the reaction time is 12-24 hours.

10. Use of the bismaleimide resin according to any one of claims 1 to 3 in the preparation of thermosetting materials.

Citation Information

Patent Citations

  • Extremely tough thermosetting bismaleimide resin systems

    CA2025039A1

  • Curable resin composition for sealing liquid crystal

    CN106062075A

  • Debondable adhesives and the high temperature use thereof

    CN108699411A

  • Force-induced responsive supramolecular polymer

    CN111378144A

  • BMI-containing insulation paste composition and application thereof

    CN117844434A